AB0686 Results of the multinational e-mail survey regarding follow up of patients with l raynaud's phenomenon. (23rd January 2014) - Foeldvari, I.
Abstract : Background: Secondary Raynaud phenomenon is an orphan disease in childhood. Currently there are no guidelines how to follow these patients and what is the most sensitive sign to differentiate between primary and secondaryRaynaud's phenomenon. In this survey special issues of this diseases and follow up concepts were surveyed. Objectives: To learn about the clinical practice regarding diagnosis and follow up concepts fro primary and secondary Raynaud's phenomenon Methods: Members of the paediatric rheumatology e-mail board and of the juvenile scleroderma working group of the PRES were asked to fill out a survey with 3 items regarding diagnosis and follow up of primary and secondary Raynauds phenomenon. Results: 28 colleagues responded to the survey with a wide spread geographic distribution. 3 questions were asked and the following responses received. If you see a patients with Raynaud's- phenomenon how often you see them for follow up: 14 of the centres followed the patient every 6 months, 7 every 3 months, 2 centres every two months and other 2 for every 12 months. Which findings do you find helpful to define secondary Raynauds? - you can give several choices: 23 of the centres found a positive nailfold capillaroscopy findings, 12 ANA positivity and 10 antiphospholipid positivity as an important sign for secondary Raynaud's phenomenon. 3 centres considered any sign of rheumatic disease supportive. If you see a patients with secondary Raynaud's phenomenon how often you see them for follow up: 16 of the centres followed the patients every 3 months, 3 of the centres every 6 months, two of the centres every 2 months. 3 of the centres made the follow up dependent in the clinical symptoms. Conclusions: The range of follow up periods differs widely between the centres. Regarding supportive sign for secondary Raynaud's a positive nailfold capillaroscopy finding appeared to be the most important sign. Prospective collection of clinical data of patients with primary and secondary Raynaud's phenomenon would help us to better understand, the most rational way to follow this patients Disclosure of Interest: None Declared